Features of attracting foreign investments - Gutkevych, Svitlana (My University, 2024)
World experience has shown that foreign investment has advantages over other forms of financing economic sectors. The country’s economy responds to changes in the global financial market. Therefore, the internal economic development of the country depends on the inflow of foreign capital in the form of loans and investments; changes in world commodity prices, interest rates and foreign exchange rates; level of use of achievements of scientific and technical progress.

Міжнародний досвід показав, що іноземні інвестиції мають переваги перед іншими формами фінансування галузей економіки. Економіка країни реагує на зміни на світовому фінансовому ринку. Тому внутрішній економічний розвиток країни залежить від надходження іноземного капіталу у вигляді кредитів та інвестицій; зміни світових цін на товари, процентних ставок і курсів іноземних валют; рівень використання досягнень науково-технічного прогресу.
Keywords: кафедра міжнародної економіки; foreign investment; investment climate; state regulation; іноземні інвестиції; інвестиційний клімат; державне регулювання